Centers for permanent healthcare education: an analysis on the experience of social players in the north of the state of Paraná¹ - Sônia Cristina Stefano Nicoletto; Fernanda de Freitas Mendonça; Vera Lúcia Ribeiro de Carvalho Bueno; Eliane Cristina Lopes Brevilheri; Daniel Carlos da Silva e Almeida; Lázara Regina de Rezende; Gisele dos Santos Carvalho; Alberto Durán González (Faculdade de Medicina de Botucatu (Unesp), 2010)
The policy of continuing healthcare education (CHE) aims to develop healthcare workers. With the objective of analyzing the process of implementing and developing the policy in Paraná, a qualitative study involving the six regions of this state is being concluded. This paper relates to the results from the northern region, focusing on the "experiencing CHE" category. In December 2006, two focus groups were conducted involving representatives from management, training, attendance and participation. The data underwent thematic content analysis. The first CHE encounters aroused feelings of mistrust and resistance, and the center was understood as a means of enabling courses and funding sources. There was a diversity of interests and little negotiating capacity. During the process, the study participants began to talk, reflect and participate. Their teamwork was a positive experience. This experience allowed them to recognize the power of CHE for linking and mobilizing different players.